Colorectal malakoplakia in a child presenting as multiple polyposis coli - Meena N Jadhav; Rashmi K Patil; Shreekant K Kittur; Jayalaxmi yadav (Wolters Kluwer Medknow Publications, 2015)
Malakoplakia of the gastrointestinal tract is a rare chronic inflammatory disorder, usually affecting the descending colon, sigmoid colon and rectum. It is commonly seen in adults. Only few cases have been reported in children. We report a case of malakoplakia of colon and rectum in a 7-year-old child who presented with multiple polyposis coli.